PELATIHAN PEMBUATAN PORTOFOLIO INSTRUMEN STANDAR ISI PADA BORANG AKREDITAS PAUD DI TK KHOIRIYATUSSIBYAN - Ifa Aristia Sandra; Sumadi Sumadi; Rista Dwi Permata; Dwi Imam Efendi (STAI Darul Qalam Tangerang, 2022)
Each PAUD (Early Childhood Education) must conduct a self-evaluation to measure the ability to meet the National Education Standards properly. This measure is then categorized in the form of institutional accreditation. Accreditation for the community is very important because the community is the main customer of educational institutions. The results of accreditation can describe the quality of an institution. Thus, the community can know and choose which institution to send their children to. But unfortunately, as we know, even the Ministry of Education and Culture also admits that many PAUDs in Indonesia are not accredited yet. This is also due to the lack of PAUD facilities and infrastructure itself in more than 30,000 villages. Out of a total of around 34 million early childhood children, only 30 percent have received their right to attend PAUD. There are more than 20 million unserved early childhood children, which belong to the 30,000 villages. So it is necessary to conduct training in the manufacture of accreditation instruments to equip early childhood institutions to improve quality, effectiveness, efficiency and innovation